Unprecedented melioidosis cases in northern Australia caused by an Asian Burkholderia pseudomallei strain identified by using large-scale comparative genomics - Price, E.P; Sarovich, D.S.; Smith, E.J.; MacHunter, B.; Harrington, G.; Theobald, V.; Hall, C.M; Hornstra, H.M; McRobb, E.; Podin, Y.; Mayo, M.; Sahl, J.W; et al. (American Society for Microbiology, 2015)
Melioidosis is a disease of humans and animals that is caused by the saprophytic bacterium Burkholderia pseudomallei. Once thought to be confined to certain locations, the known presence of B. pseudomallei is expanding as more regions of endemicity are uncovered. There is no vaccine for melioidosis, and even with antibiotic administration, the mortality rate is as high as 40% in some regions that are endemic for the infection. Despite high levels of recombination, phylogenetic reconstruction of B. pseudomallei populations using whole-genome sequencing (WGS) has revealed surprisingly robust biogeographic separation between isolates from Australia and Asia. To date, there have been no confirmed autochthonous melioidosis cases in Australia caused by an Asian isolate; likewise, no autochthonous cases in Asia have been identified as Australian in origin. Here, we used comparative genomic analysis of 455 B. pseudomallei genomes to confirm the unprecedented presence of an Asian clone, sequence type 562 (ST-562), in Darwin, northern Australia. First observed in Darwin in 2005, the incidence of melioidosis cases attributable to ST-562 infection has steadily risen, and it is now a common strain in Darwin. Intriguingly, the Australian ST-562 appears to be geographically restricted to a single locale and is genetically less diverse than other common STs from this region, indicating a recent introduction of this clone into northern Australia. Detailed genomic and epidemiological investigations of new clinical and environmental B. pseudomallei isolates in the Darwin region and ST-562 isolates from Asia will be critical for understanding the origin, distribution, and dissemination of this emerging clone in northern Australia.